PENGARUH BENZYL AMINO PURIN DAN ARANG AKTIF TERHADAP TINGGI TUNAS DAN JUMLAH TUNAS KRISAN (Chrysanthemum daisy L.) SECARA IN VITRO - Nurmayulis .; Susiyanti .; Khafas Bastian (Jurnal Agroekoteknologi, 2010)
ABSTRACTThis research was about the growth of in vitro Chrysanthemum daisy L.) on medium which used Benzyl Amino Purine (BAP) and activated  charcoal. Research aim to determine the growth of Chrysanthemum plant on different concentrations of BAP and active charcoal into medium. This reseach was done in culture laboratory, in Association of Plant Forest Seed and Plantation Banten Province.  This research used factorial experiment which arranged in Randomized  Complete Design. The treathment consist of two factor. The first factor was BAP concentrate which were consist of five level include 0 ppm concentrate; 0.5 ppm; 1.0 ppm; 1.5 ppm; and 2.0 ppm. Second factor was activated charcoal dossage which consist four level included dossage 0 g L-1; 1 g L-1; 2 g L-1; and 3 g L-1. Based on the result of research showed that interaction in BAP and active charcoal influenced hight bud, but did not influence the number of shoots.  The best high of shoots on the age 1-5 WAP (Week After Plants) which given BAP and activated charcoal in vitro medium consist act combination 1-5 WAP A0B1 (0.5 ppm BAP without active charcoal). Singular factor BAP and active charcoal showed that act without BAP and activated charcoal produced the best at 5 WAP.Keywords: Chrysanthemum  plant, BAP, and Activated charcoal.